What Does New Haven Have to Do with Lubbock? Texts, Techniques, and Sociology - Cukrowski, Kenneth L. (Teaching theology and religion, 2000)
This note examines some pedagogical strategies for the formation of students who read the Bible both confessionally and critically. Some students in both church-related and secular colleges and universities enter courses with confessional views of the Bible that inspire a literal interpretation of the text, what the author calls a flat reading. Teachers struggle to lead students to a more nuanced view of the text in a way that is both sensitive to the students' development and academically responsible. The author indicates how he approaches this challenge through: (1) a discussion of texts that have been used to enable students to see the nature of the biblical text and to transform their understanding of it; (2) a description of techniques and exercises that work toward the same goal; and (3) reflection on the application of sociological research on group change in the transformation of individuals.